ANALISIS KINERJA MESIN PENCACAH SAMPAH DENGAN VARIASI KECEPATAN PUTAR MOTOR LISTRIK - Zebtomen Siringoringo; Sigiet Haryo Pranoto; Anis Siti Nurrohkayati; Ananda Sylvano (JURNAL CRANKSHAFT, 2026)
This study aims to analyze the effect of variations in the rotational speed of an electric motor on shredding capacity and the average size of shredded output in a plastic waste shredding machine. The method used is an experimental approach by conducting direct tests on a shredding machine using a single-phase electric motor with a power of 2 HP, with speed variations of 600 rpm, 900 rpm, and 1200 rpm. The test materials include plastic bottles, plastic bags, and cardboard, with a shredding time of 2 minutes for each test. The observed parameters include the mass of shredded material, shredding capacity (kg/h), and the average size of the shredded output. The results show that the highest shredding capacity for plastic bottles and plastic bags was achieved at a speed of 900 rpm, reaching 25.20 kg/h and 13.50 kg/h, respectively, while for cardboard material, the highest capacity was obtained at 600 rpm, reaching 28.59 kg/h. These findings indicate that increasing rotational speed does not always result in the highest shredding capacity for all materials, as the physical characteristics of the materials influence the shredding performance.